BUILDING STUDENTS’ RESILIENCE: STRATEGIES TO OVERCOME STUDENTS’ LEARNING CHALLENGES (PIONIR: JURNAL PENDIDIKAN, 2025)
In the face of increasing academic demands and rapidly evolving educational environments, student resilience has become a serious factor in determining academic success and emotional well-being. This study explores practical strategies that have proven effective in building student resilience in schools include social-emotional learning approaches, character education, and guidance and counselling services that focus on developing resilience. to build and strengthen students’ resilience in overcoming various learning challenges, such as academic pressure, lack of motivation, limited resources, and external distractions. Drawing on both qualitative and quantitative data, the research identifies effective interventions implemented by educators, including the integration of growth mindset practices, peer mentoring, flexible learning models, and socio-emotional learning (SEL) approaches. Findings suggest that resilience can be nurtured through consistent support systems, positive reinforcement, and the development of self-regulation and adaptive coping skills. The study concludes that fostering resilience not only enhances students’ academic performance but also equips them with lifelong skills for facing future adversities.Keywords: Student Resilience, Resilience Development Strategies, Learning Challenges.